Effectiveness of Early Detection Using KSDS in Pregnant Women Against Preeclampsia at the Managaisaki City Health Center, Tolitoli Regency - Hasni, Hasni; Saman, Saman; Evie, Sova; Ra'bung, Alfrida Semuel; Suswinarto, Dwi Yogyo; Enggar, Enggar (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Preeclampsia is a leading cause of maternal mortality, second only to hemorrhage. Early detection of preeclampsia risk during pregnancy is crucial for timely prevention and treatment. The Dhiana Setyorini Scorecard (KSDS) is a simple tool that health professionals and the general public can use to identify preeclampsia risk in pregnant women. This study aimed to evaluate the effectiveness of KSDS for early detection of preeclampsia in pregnant women at the Managaisaki City Health Center in Tolitoli Regency. A non-experimental cohort design was employed, with a sample of 86 second-trimester pregnant women selected using accidental sampling. The KSDS was used as the research instrument, and data were analyzed using Fisher's test. The results showed that no cases of preeclampsia were observed among women in the low-risk group. In contrast, 7 out of 14 pregnant women with high-risk factors experienced preeclampsia (p<0.05), indicating a significant association between risk factors and preeclampsia incidence. The study concludes that KSDS is effective in the early detection of preeclampsia risk. Integrating KSDS into prenatal screening protocols and training healthcare workers on its use and interpretation can improve maternal and infant safety during pregnancy. Further research should consider the potential impact of confounding variables and increase the sample size for more comprehensive findings.